2020
DOI: 10.1002/tox.23025
|View full text |Cite
|
Sign up to set email alerts
|

Shh‐Yap signaling controls hepatic ductular reactions in CCl4‐induced liver injury

Abstract: Carbon tetrachloride (CCl4) exposure can induce hepatic ductular reactions. To date, however, the related mechanism remains largely unknown. Sonic hedgehog (Shh) and Yes‐associated protein (Yap) signaling are correlated with liver injury and regeneration. Herein, we investigated the role of Shh and Yap signaling in the fate of ductular reaction cells in CCl4‐treated livers and the possible mechanisms. Wild‐type and Shh‐EGFP‐Cre male mice were exposed to CCl4 (2 mL/kg), and then treated with or without the Shh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Previous studies have shown that Yap signalling activity is positively correlated with the activation of ductular reactions (Jin et al 2021 ). As such, we explored Yap signalling pathway activity and target gene expression levels in the livers of 18–20-day-old G6pc −/− and WT mice.…”
Section: Resultsmentioning
confidence: 95%
“…Previous studies have shown that Yap signalling activity is positively correlated with the activation of ductular reactions (Jin et al 2021 ). As such, we explored Yap signalling pathway activity and target gene expression levels in the livers of 18–20-day-old G6pc −/− and WT mice.…”
Section: Resultsmentioning
confidence: 95%
“…CCl 4 contamination in the environment can be absorbed by the body. 33 The purpose of this study was to investigate the protective effect of LBB and LBBET against CCl 4 -induced liver injury. In this study, it was confirmed that liver damage caused by CCl 4 can be remarkably alleviated by using LBB and LBBET as raw materials.…”
Section: Discussionmentioning
confidence: 99%
“…The Hh pathway was recently shown to control the activity of YAP in HSCs, and blocking Hh pathway and YAP activation prevented HSCs transdifferentiating into MF (Du et al 2018). Furthermore, the cross talking between Shh and Yap signaling are correlated with liver injury and Yap is known to be a downstream effect of the Shh pathway in fibrotic livers (Jin et al 2021). Liver injury triggers the activation of the Hh pathway and Yap, both of which switch from typical low or absent expression levels to high activities (Liu et al 2019; Swiderska‐Syn et al 2016).…”
Section: Discussionmentioning
confidence: 99%